Analysing the Conditions of SMEs Regarding Quality Assurance in Hungary and the European Union - Popovicsné Szilágyi, Zita; Menyhárt, József (International Journal of Engineering and Management Sciences, 2022)
Nowadays, small and medium sized enterprises (SME) have a relatively large task and expectation caused by the appearing of populated large foreign-owned enterprises in our country. In order that they will be able to cooperate with them and be able to join and integrate into the value chain they supply they must meet the high quality of standards. Obtaining then preserving quality certificates is essential for this. It can be fulfilled exclusively with thorough screening and problem identification.This situation is exacerbated continuously by globalization in which each sector is involved. It means that they must remain competitive globally. Although in our country most of the small and medium sized enterprises bears the specific characteristics of family businesses innovation may not be avoided if they intend to stay competitive. To fulfil this quality assurance is one of its integral part.